MAMMALS - Jones, Grace, 1990- (King's Lynn, Norfolk : The Secret Book Company, 2019)
Vowels can say their names: A-E-I-O-U. These vowel sound can be spelled many different ways, including vowel teams.Discover how these long vowels and vowel teams can be used to build words.
Includes index.
Ages 4-8.
Keywords: Mammals -- Juvenile literature